2022
DOI: 10.1088/1742-6596/2151/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Induced stalled flow due to roughness sensitivity for thick airfoils in modern wind turbines

Abstract: The mid-span region of wind turbine blades can be thickened to fulfil the structural requirements of the blade. Hence, thick airfoils, that were designed to operate at the root region of the blade, are moved to the mid-span region. This could not imply remarkable variations of the blade performance once its surface is smooth. However, the sensitivity of thick airfoils to roughness could cause significant aerodynamic impacts such as flow separation. This research aims to quantify the impact of the blade thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The chosen reference wind turbine was used in a complementary study [3] in which different blade designs were generated via the interpolation of two thickness distributions. The interpolation factor was denoted as F and a value of 0.5 is selected which is in line with the literature statements [24,25] that modern blades tend to be relatively thicker in their outer part than old blades.…”
Section: Methodsmentioning
confidence: 99%
“…The chosen reference wind turbine was used in a complementary study [3] in which different blade designs were generated via the interpolation of two thickness distributions. The interpolation factor was denoted as F and a value of 0.5 is selected which is in line with the literature statements [24,25] that modern blades tend to be relatively thicker in their outer part than old blades.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, a relatively stronger APG is given at an AoA of 0°, which challenges the validation even more. The experiments of Gutierrez et al 5 constitute the reference for this study because they offer the framework to understand the steady 2D‐RANS failure and also quantify the impact of flow separation on the power production of a modern wind turbine 6 . They will be referred to as LSLT in the next part of the paper since they have been conducted at the low‐speed low‐turbulence wind tunnel of TU Delft.…”
Section: Methodsmentioning
confidence: 99%
“…30 The simulations failed in predicting the flow separation independently of the boundary condition used in the LE to emulate roughness. Later, aeroelastic calculations 6 revealed that the operational AoA was 5 at the mid-span region where thick airfoils can be located in case of thick blades. The numerical study 30 demonstrated that the steady 2D-RANS approach mainly fails in predicting the flow separation over the airfoil PS for this AoA of 5 .…”
Section: Pressure-gradient Adaptationmentioning
confidence: 99%
See 2 more Smart Citations